THE ROLE OF ORGANIZATIONAL COMMUNICATION AS A MEDIATION OF CHANGE MANAGEMENT AND EMPLOYEE PERFORMANCE AT THE SPECIAL HOSPITAL OF SURGERY KARIMA UTAMA SURAKARTA - Sudarwati Sudarwati; Istiatin Istiatin; Ida Aryati Diyah PW; Setiyo Nugroho (Universitas Muhammadiyah Yogyakarta, 2022)
This research aims to look at and analyze the effect of change management on employee performance and measure the role of organizational communication as a mediation variable for the impact of change management on employee performance at the Hospital of Special Surgery Karima Utama Surakarta. This model involved the training variable as the supporting variable. This research was relevant to hospitals; from several 350 employees, 100 employees were selected as samples using purposive sampling techniques. The study was analyzed using Partial Least Square (PLS) with SmartPLS3 software. The results showed that change management had a significant and positive effect on organizational communication. Training had a significant and positive impact on organizational communication. Organizational communication, change management, and training had a significant and positive impact on employee performance. Organizational communication proved to be a partial mediation of the development of exercise on employee performance. Organizational communication was also proven to be a partial mediation of the impact of change management on employee performance.